The Development of the Employer Brand in the Labour Market - Aleksandra Marcikic Horvat; Radovan Pejanović; Zoran Ćirić; Bojana Ćirić; Otilija Sedlak; Leposava Grubić-Nešić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Nowadays, the lack of high qualified staff is more conspicuous than ever before. The development of new knowledge and professions is followed by the modern technological changes, enormous usage of Internet and development of artificial intelligence. These trends have led to changes in the behaviour and access of both sides in the labour market. Candidates who have specific knowledge, skills and experience have the opportunity to choose the companies they want to work in, setting the conditions for employers. Companies, employers, who need some special skills are forced to make an effort to stand out and attract the attention of the target group. Therefore, the branding activities of the employer became crucial in a modern labour market. The aim of the paper is to identify the dimensions of attractiveness in branding employers and the levels of importance of each dimension. The results of the survey indicate that candidates are looking for many additional information about the employer. Each generation has certain ways and channels of gathering information that it considers credible. If employers do not recognize or ignore those channels, they miss the possibility of establishing and building relationships with candidates before employment itself.
Keywords: M31; M54; O15; 330; branding employers; labour market; marketing; human resources; economy